KEPEMIMPINAN KEPALA DESA DALAM MEWUJUDKAN DESA MANDIRI DI DESA BOJONGMALAKA KECAMATAN BALEENDAH KABUPATEN BANDUNG - Chintiya Citra Purnama; Dadan Kurnia; Arlan Siddha (Jurnal Caraka Prabu, 2019)
The research entitled "Village Head Leadership in Creating Independent Villages in Bojongmalaka Village, Baleendah District, Bandung Regency" This research is motivated by looking at the condition of Bojongmalaka Village which was chosen as the best in Baleendah District, Bandung Regency so that this village will create an independent village.The research methodology used is descriptive research method with a qualitative approach, with the intention of focusing on the phenomena and problems that occur at the time the research was conducted. Data obtained from observations, documentation and interviews with key informants as primary data. Key informants were determined based on several criteria, at least 3 sources were used as research objects, namely the Village Head, Village Secretary, and the Head of the Village Consultative Body (BPD). The data is processed by means of data reduction, data categorization, synthesization and formulation of working hypotheses as the last step in the data compilation process.The results showed that the leadership of the village head in realizing an independent village in the village of Bojongmalaka, Baleendah District, Bandung Regency has been achieved well and optimally. However, the program being carried out is still in the process of turning the village into an independent village. The village head and village officials are working on the concept and program of the village in order to get maximum results so that this village can be said to be an independent village. Keywords: leadership, village head, independent village